Stabilization of heavy metals in MSWI fly ash with a novel dithiocarboxylate-functionalized polyaminoamide dendrimer. (15th March 2020) - Zhang, Manling; Guo, Mengru; Zhang, Bingru; Li, Fengting; Wang, Hongtao; Zhang, Hebin
Highlights: Heavy metal stabilization, using newly developed polymers, PAMAM-0G-DTC, maintained the long term stability of heavy metals at lower doses. Leachability was analyzed in accordance with different extraction procedures. Solidifying agents with multiple dithioacid groups bound with metals efficiently. Abstract: A novel heavy metal chelating agent, dithiocarboxylate-functionalized polyaminoamide dendrimer (PAMAM-0G-DTC), was evaluated for the stabilization of heavy metals from municipal solids waste incineration (MSWI) fly ash. PAMAM-0G-DTC achieved overall stabilization performance at a lower dosage (3% w/w) and a wider pH range (2–13) compared to conventional chelating agents such as sodium dimethyl dithiocarbamate (SDD) and dithiocarboxylate-functionalized tetraethylenepentamine (TEPA-DTC). The leaching toxicity of Pb and Cd in the MSWI fly ash by PAMAM-0G-DTC stabilization met the landfill requirements but could not be achieved by SDD and TEPA-DTC even at a 10 wt% concentration. Sequential chemical extraction of fly ash before and after stabilization shows that PAMAM-0G-DTC can be combined with active heavy metals in water-soluble, interchangeable, and carbonate states to form more stable heavy metals in organic and residual states. Mechanistic studies show that multiple PAMAM-0G-DTC molecules can combine with multiple heavy metals to form three-dimensional network-like super-molecular compounds with an infinite extension of space size. This makes the heavy metals more stable and embedded in the network-like super-molecular structure, thus minimizing the potential risk of leaching. Overall, by forming more geochemically stable phases, the treatment of fly ash with PAMAM-0G-DTC has a strong ability to reduce the toxic leaching of heavy metals at a lower dosage and suppress the risk of secondary pollution in a landfill at a wide range of pH values (2–13).